Hybrid binary quantization and BP network on action mechanism. Issue 1 (June 2021) - Jiang, Chenhui; Shangguan, Zhiyang; He, Huan; Zhang, Jinglou; Ping, Jing; Li, Naiwei
Abstract: BP neural network is a kind of artificial neural network, which is mainly used in function approximation, model recognition, classification and data compression. In the case of limited analysis ability of traditional research methods, BP neural network can overcome the problems of nonlinear relationship. In this paper, the improved BP neural network was used to predict the properties. The data processing of the properties, tastes and was carried out by binary quantization. The prediction results' correct rate was 87.5%.